2019
DOI: 10.1007/s00018-019-03399-5
|View full text |Cite
|
Sign up to set email alerts
|

HAS3-induced extracellular vesicles from melanoma cells stimulate IHH mediated c-Myc upregulation via the hedgehog signaling pathway in target cells

Abstract: Intercellular communication is fundamental to the survival and maintenance of all multicellular systems, whereas dysregulation of communication pathways can drive cancer progression. Extracellular vesicles (EVs) are mediators of cell-to-cell communication that regulate a variety of cellular processes involved in tumor progression. Overexpression of a specific plasma membrane enzyme, hyaluronan synthase 3 (HAS3), is one of the factors that can induce EV shedding. HAS3, and particularly its product hyaluronan (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 105 publications
0
20
0
Order By: Relevance
“…The role of HAS3 in tumor progression is not related to its enzymatic activity, eventually altered by post-translational modifications, but more to its involvement in the induction of extracellular vesicles (EVs) shedding. Arasu et al observed that increased amounts of EVs derived from GFP-HAS3 expressing metastatic melanoma cells induced HA secretion, proliferation, and invasion of target keratinocytes and primary melanoma cell line [ 64 ]. As described here, these HAS3-rich EVs contained high amounts of HA and, importantly, CD44 that participated in the regulation of EV binding to target cells [ 64 ].…”
Section: Hyaluronan In Tme: a Simple Extracellular Macromolecule With A High Impact In Tumor Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of HAS3 in tumor progression is not related to its enzymatic activity, eventually altered by post-translational modifications, but more to its involvement in the induction of extracellular vesicles (EVs) shedding. Arasu et al observed that increased amounts of EVs derived from GFP-HAS3 expressing metastatic melanoma cells induced HA secretion, proliferation, and invasion of target keratinocytes and primary melanoma cell line [ 64 ]. As described here, these HAS3-rich EVs contained high amounts of HA and, importantly, CD44 that participated in the regulation of EV binding to target cells [ 64 ].…”
Section: Hyaluronan In Tme: a Simple Extracellular Macromolecule With A High Impact In Tumor Progressionmentioning
confidence: 99%
“…Arasu et al observed that increased amounts of EVs derived from GFP-HAS3 expressing metastatic melanoma cells induced HA secretion, proliferation, and invasion of target keratinocytes and primary melanoma cell line [ 64 ]. As described here, these HAS3-rich EVs contained high amounts of HA and, importantly, CD44 that participated in the regulation of EV binding to target cells [ 64 ]. In addition to cell functions’ associated genes induction, target cells may undergo EMT.…”
Section: Hyaluronan In Tme: a Simple Extracellular Macromolecule With A High Impact In Tumor Progressionmentioning
confidence: 99%
“…Regarding its signaling properties, it has been shown that HA plays an important role during embryonic development regulating cell migration, shape, and proliferation ( Spicer and Tien, 2004 ). HAS3 is the most active enzyme of the HAS family and polymerizes shorter HA chains ( Itano et al, 1999 ; Itano and Kimata, 2002 ) that stimulates cell signaling, proliferation, and epithelial-to-mesenchymal transition in cancer models ( Kultti et al, 2014 ; Kuo et al, 2017 ; Arasu et al, 2019 ). HAS3 expression is higher in the dental epithelium than the mesenchyme, with the distribution of CD44 appearing complementary to HAS3 in the dental epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…(O)MVs bind to the bronchial epithelium, as shown for P. aeruginosa OMVs [ 69 ], and alveolar epithelial cells, as demonstrated for A. baumannii OMVs and S. pneumoniae MVs [ 51 , 70 ]. Notably, for EVs an important role of CD44 in the EV binding process has been well documented [ 71 , 72 ]. As CD44 is the hyaluronic receptor, and hyaluronan forms an important constituent of both the alveolar epithelial glycocalyx and airway mucus, a similar “attachment chemistry” may also exist in (O)MVs but remains to be identified [ 73 , 74 ].…”
Section: The Interaction Of (O)mvs With the Respiratory Epithelium—a First Step In Immunoactivationmentioning
confidence: 99%